The features and training of compulsory exercise of martial arts - Feng, C. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction The compulsory exercises are the main part of the series of skills and tricks in Martial Arts, it have strict demands on the physical stamina, skill and will of athletes during the process of competition. At present even the most athletic competitors have a low success rate during the competition. Therefore, to raise the success rate is the key factor that decide the results, and it`s also the focal point and most difficult aspect during training. This thesis delves further into the use of training regimen to raise the success rate of the compulsory exercise, puts forward a monitoring index of the training regimen. Methods We took 59 athletes as the subjects of our study, used the three-dimensional space recorder`s analyze, heart rate monitor, blood lactic acid test instrument, and SPSS statistics to analyze the data. This allowed us to set up an ideal technical movement model, exercise intensity model of the Martial Arts competition, to practice the compulsory exercise under the conditions of mock competitions exercise intensity. Result (1) The success rate of compulsory exercise in the Martial Arts 's final rounds are lower than 7%. The statistics indicates that those who got good marks had fewer deductions, and those who got bad marks had more deductions. (2) Sums up the main technical specification of the compulsory exercise, puts forward the main evaluated index of individual special courses quality, then test and evaluate at regular intervals. (3) Set up the kinematics index diagnosis modal and image diagnosis modal for the compulsory exercise and produce ideal movements VCD and other teaching material, the athletes are in training of ideal movements. (4) Although the success rate of ten times single compulsory exercise practice reaches 90%, the success rate in competition is still low. puts forward three kinds of main monitoring index of training methods and provides the reference to the training before competition. Conclusion (1) The technical combination of compulsory exercise is complicated. It`s the weak link of the outstanding athletes nowadays. Attach great importance to the training of compulsory exercise, to raise the success rate is the key factor to raise the competition`s score. (2) It is an effective measures for raising the compulsory exercise success rate to train the athletes scientifically, through setting up the evaluated index of special courses quality, technical diagnosis model and the monitoring index of exercise intensity. (3) It is the focal point of the training of compulsory exercise before competition to train the athletes under the condition of a mock competition, and ask the athletes try to succeed in the actual combatant training of compulsory exercise at one time.Introduction The compulsory exercises are the main part of the series of skills and tricks in Martial Arts, it have strict demands on the physical stamina, skill and will of athletes during the process of competition. At present even the most athletic competitors have a low success rate during the competition. Therefore, to raise the success rate is the key factor that decide the results, and it`s also the focal point and most difficult aspect during training. This thesis delves further into the use of training regimen to raise the success rate of the compulsory exercise, puts forward a monitoring index of the training regimen. Methods We took 59 athletes as the subjects of our study, used the three-dimensional space recorder`s analyze, heart rate monitor, blood lactic acid test instrument, and SPSS statistics to analyze the data. This allowed us to set up an ideal technical movement model, exercise intensity model of the Martial Arts competition, to practice the compulsory exercise under the conditions of mock competitions exercise intensity. Result (1) The success rate of compulsory exercise in the Martial Arts 's final rounds are lower than 7%. The statistics indicates that those who got good marks had fewer deductions, and those who got bad marks had more deductions. Sums up the main technical specification of the compulsory exercise, puts forward the main evaluated index of individual special courses quality, then test and evaluate at regular intervals. Set up the kinematics index diagnosis modal and image diagnosis modal for the compulsory exercise and produce ideal movements VCD and other teaching material, the athletes are in training of ideal movements. Although the success rate of ten times single compulsory exercise practice reaches 90%, the success rate in competition is still low. puts forward three kinds of main monitoring index of training methods and provides the reference to the training before competition. Conclusion (1) The technical combination of compulsory exercise is complicated. It`s the weak link of the outstanding athletes nowadays. Attach great importance to the training of compulsory exercise, to raise the success rate is the key factor to raise the competition`s score. (2) It is an effective measures for raising the compulsory exercise success rate to train the athletes scientifically, through setting up the evaluated index of special courses quality, technical diagnosis model and the monitoring index of exercise intensity. (3) It is the focal point of the training of compulsory exercise before competition to train the athletes under the condition of a mock competition, and ask the athletes try to succeed in the actual combatant training of compulsory exercise at one time.